Emerging understandings of the role of exosomes in atherosclerosis - Zena Wehbe (16328843) (2024)
Atherosclerosis remains a major contributor to cardiovascular disease, the leading cause of global morbidity and mortality. Despite the elucidation of several molecular, biochemical, and cellular aspects that contribute to the etio‐pathogenesis of atherosclerosis, much remains to be understood about the onset and progression of this disease. Emerging evidence supports a role for exosomes in the cellular basis of atherosclerosis. Indeed, exosomes of activated monocytes seem to accentuate a positive feedback loop that promotes recruitment of pro‐inflammatory leukocytes. Moreover, in addition to their role in promoting proliferation and invasion of vascular smooth muscle cells, exosomes can also induce neovascularization within lesions and increase endothelial permeability, two important features of fibrous plaques. Depending on their sources and cargo, exosomes can also induce clot formation and contribute to other hallmarks of atherosclerosis. Taken together, it is becoming increasingly evident that a better understanding of exosome biology is integral to elucidating the pathogenesis of atherosclerosis, and may thus provide insight into a potentially new therapeutic target for this disease. Other Information Published in: Journal of Cellular Physiology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/jcp.31454